2019
DOI: 10.1039/c8an01431k
|View full text |Cite
|
Sign up to set email alerts
|

Paper-based platform for detection by hybridization using intrinsically labeled fluorescent oligonucleotide probes on quantum dots

Abstract: Paper-based platform for the selective detection of DNA targets by hybridization using FRET between intrinsically labeled fluorescent DNA probes and quantum dots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The paper-based sensor enabled genomic DNA's identification for Escherichia coli and Campylobacter jejuni, with the LOD of 2 × 10 3 copies/μL. Other μPads for nucleic acid detection [188][189][190][191][192] have been summarized in Table 2. Another important application for μPads is to directly detect cells.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…The paper-based sensor enabled genomic DNA's identification for Escherichia coli and Campylobacter jejuni, with the LOD of 2 × 10 3 copies/μL. Other μPads for nucleic acid detection [188][189][190][191][192] have been summarized in Table 2. Another important application for μPads is to directly detect cells.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…(f) Paper-immobilized quantum dot-oligonucleotides and free Cy3-oligonucleotides contain different DNA segments complementary to the target gene fragment. In a sandwich format, the target gene serves as a hybridization bridge for the QD-oligonucleotide and Cy3-oligonucleotide, which in turn enables FRET between QD and Cy3 [84][85][86][87]; (g) A Cy3-labeled kanamycin-specific aptamer partially hybridizes to an anchor/connector oligonucleotide immobilized on glass. The connector oligonucleotide is conjugated to Cy5.…”
Section: Bioluminescence-resonance-energy-transfer-based Systemsmentioning
confidence: 99%
“…Krull and co-workers developed different sensing systems deployed at PON, using a paper-based design. The biosensors are based on the transduction of nucleic acid hybridization [84,85,87,91,92] and both a direct and a sandwich format assay were developed, both based on paper-immobilized quantum dot-oligonucleotide conjugates (Figure 4f, sandwich assay format shown) [92,93]. Hybridization events in both formats brings the QD into close proximity with Cy3 [92].…”
Section: Fluorescence-resonance-energy-transfer-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a FRET experiment for a multicolor paper-based platform has been successfully applied to detect target DNA using green and red-emitting GSH-capped QDs with the limit of detection (LOD) in the range of femtomole [ 16 ]. Furthermore, other research has also been reported for the detection of oligonucleotide targets via FRET principle [ [26] , [27] , [28] , [29] , [30] ]. Till now, no sensor-based approach like GSH-CdTe-QDs probes has been reported for the detection of V617F mutation of JAK2 gene.…”
Section: Introductionmentioning
confidence: 99%